Earth materials : introduction to mineralogy and petrology - Klein, Cornelis; Philpotts, Anthony R. (Cambridge Cambridge University Press, 2017)
"This concise, accessible, market-leading textbook brings together the wide-ranging fundamentals students need to understand rocks and minerals, and shows them how they relate to the broader Earth, materials and environmental sciences. Designed specifically for one-semester courses, it is beautifully illustrated to explain the key concepts in mineralogy and petrology. This edition has been fully updated based on classroom experience, and new features include a completely new chapter providing an elementary introduction to thermodynamics, kinetics, radioactive decay and absolute dating; new mineral descriptions and many new stunning color photographs; and a new section on hydraulic fracturing and discussion of some of its most serious potential environmental consequences. The book uses stunning photos of mineral specimens and rock thin sections to help students build a core understanding. It also creates a highly effective learning experience through close integration of clear illustrations with engaging text, and helps students to easily visualize crystal structures through the CrystalViewer's 3D software, available online"--
"This concise, accessible, market-leading textbook brings together the wide-ranging fundamentals students need to understand rocks and minerals, and shows them how they relate to the broader Earth, materials and environmental sciences. Designed specifically for one-semester courses, it is beautifully illustrated in full colour to explain the key concepts in mineralogy and petrology. This revision has been fully updated based on classroom experience. Including a completely new chapter providing an elementary introduction to thermodynamics, kinetics, radioactive decay and absolute dating, this new edition also features new mineral descriptions and many new stunning color photographs. A new section on hydraulic fracturing and discussion of some of its most serious potential environmental consequences has also been added. Stunning photos of mineral specimens and rock thin sections help students build a core understanding, whilst close intergration of clear illustrations with engaging text create a highly effective learning experience"--
Machine generated contents note: 1. Introduction; 2. Materials of the solid earth; 3. How are minerals identified?; 4. Fundamentals of crystal structures; 5. Introduction to crystallography; 6. Minerals and rocks observed under the polarizing optical microscope; 7. Igneous rock-forming minerals; 8. The direction and rate of natural processes: an introduction to thermodynamics and kinetics; 9. How do igneous rocks form?; 10. Igneous rocks: their mode of occurrence, classification, and plate tectonic setting; 11. Sedimentary rock-forming minerals and materials; 12. Formation, transport, and lithification of sediment; 13. Sedimentary rock classification, occurrence, and plate tectonic significance; 14. Metamorphic rock-forming minerals; 15. Metamorphic rocks; 16. Some economic minerals, mainly from veins and pegmatites; 17. Some selected earth materials resources; 18. Earth materials and human health.
Includes bibliographical references and index.
Keywords: Mineralogy -- Textbooks; Petrology -- Textbooks